Medical exposure of patients from diagnostic X-ray examinations performed in medical organizations of the Russian Federation in 2022 - A. A. Bratilova; A. N. Barkovsky (Радиационная гигиена)
The paper presents results of analysis of information on doses from medical exposure of the public in the Russian Federation in 2022, submitted via Federal Statistical Surveillance Form No. 3-DOZ “Information on doses to patients from medical X-ray examinations” to the Federal Databank on medical exposure doses, which operates on the base of Institute of Radiation Hygiene after P.V. Ramzaev, as well as received as part of radiation-hygienic passportization from the Federal Medical and Biological Agency of the Russian Federation, the Ministry of Defense of the Russian Federation, and the Federal Service for the Execution of Punishments of the Russian Federation. The data on the structure of doses from medical exposure of the public in the regions of the Russian Federation and Russia as a whole in 2022, as well as on the dynamics of these indicators for the last 5 years are presented. The average dose from medical exposure of the public of the Russian Federation in 2022 amounted to 0.86 mSv/year per one inhabitant and 0.43 mSv per one procedure. The highest values of the average dose per inhabitant in 2022 were in Moscow (1.71 mSv), in the Republic of Karelia (1.5 mSv), in the Nenetsk Autonomous District (1.32 mSv), in the Khabarovsk Krai (1.26 mSv), in the Murmansk Region (1.23 mSv) and in the Magadan region (1.20 mSv). In another 15 regions of the Russian Federation, annual effective doses from medical radiation exposure exceeded 1 mSv per inhabitant on average in 2022. The highest values of the average dose per procedure in 2022 were observed in the Republic of Adygea (0.96 mSv), in Moscow (0.74 mSv) and in the Republic of Ingushetia (0.73 mSv). The highest values of average doses were observed: for fluorography in the Republics of North Ossetia (0.18 mSv), Crimea (0.18 mSv) and Adygea (0.15 mSv), with an average value for the Russian Federation being 0.05 mSv; for radiography in the Kaliningrad (0.11 mSv) and Tver (0.11 mSv) regions, with the average value for the Russian Federation being 0.06 mSv; for fluoroscopy in Sevastopol (7.59 mSv), in the Udmurt Republic (5.97 mSv) and in the Republic of Crimea (5.75 mSv), with the average value for the Russian Federation being 2.35 mSv; for computer tomography in the Nenetsk Autonomous District (6.25 mSv), in the Republics of Karelia (5.92 mSv) and Adygea (5.43 mSv), with the average value for the Russian Federation being 3.86 mSv; for interventional examinations in the Omsk Region (16.5 mSv), in the Republic of Karelia (16.4 mSv) and in the Vladimir Region (13.7 mSv), with the average value for the Russian Federation being 4.89 mSv; for diagnostic nuclear medicine in the Vladimir region (30.1 mSv), Ivanovo region (23.2 mSv) and Rostov region (19.5 mSv), with the average value for the Russian Federation being 8.07 mSv; for other radiology procedures in the Republic of Bashkortostan (8.53 mSv), Nizhny Novgorod (7.90 mSv) and Vologda (7.40 mSv) regions, with the average value for the Russian Federation being 1.04 mSv. The maximum average dose from medical exposure per procedure exceeds the average for the Russian Federation by a factor of 2.2, and per inhabitant – by a factor of 2, which can be considered quite a satisfactory result considering the significant difference in the structure of their X-ray diagnostics.